Does a History of Migraine Affect the Rate of Thrombolysis in Young Stroke Patients? - Halvor Øygarden; Christopher Elnan Kvistad; Lars Thomassen; Ulrike Waje-Andreassen; Halvor Naess (Stroke Research and Treatment, 2013)
Background. Migraine is prevalent in young patients and a frequent stroke mimic. To distinguish stroke mimics from true stroke can be difficult, and there is a possibility of misdiagnosing a stroke as a migrainous attack in patients with migraine. We aimed to investigate if a history of migraine affects the rate of thrombolytic therapy in young stroke patients. Methods. All patients below 50 years of age admitted in the period 2006–2013 to the Bergen Stroke Centre with acute ischaemic stroke were included. The rate of thrombolytic therapy in patients with migraine was compared to patients with no history of migraine. A multivariate analysis was performed to adjust confounding factors. Results. A total of 170 young stroke patients were enrolled, 49 with migraine and 121 with no migraine. In total, 10.2% of young patients with migraine received thrombolytic therapy, compared with 26.5% of young patients with nomigraine (P=0.02). Migraine was associated with a low rate of thrombolytic therapy when adjusting for possible confounding factors (OR 0.19 CI: 0.05–0.72, P=0.02). Conclusion. Migraine is associated with a low rate of thrombolytic therapy in young patients admitted with acute ischaemic stroke. Migraine patients admitted with acute ischaemic stroke are at risk of maltreatment.